Religious affiliation as a predictor of involuntary psychiatric admission: A Brazilian one-year follow-up study - Caio Borba Casella; Alexandre Andrade Loch (Frontiers Media S.A., 2014)
Objective: The aim of this study was to analyze factors associated with the legal status at psychiatric admission of individuals with psychosis or bipolar disorder in a Latin-American cultural setting. Methods: Prospective observational study, conducted in São Paulo, Brazil. We analyzed 169 individuals with bipolar or psychotic disorder in need of hospitalization. Sociodemographic data, data on the psychiatric disorder, information about the hospital stay and data at time of discharge were collected. Their families were also contacted by telephone and interviews were conducted at 1, 2, 6 and 12 months post-discharge as a follow-up. Results: Eighty-eight patients (52%) had a voluntary admission (VA) and 81 (48%) an involuntary one (IA). The average length of admission was similar in both groups (17.4 vs. 17.3 days, p=0.22). It was significantly more common for IA patients to be admitted because of other-directed aggressiveness (47.7% vs. 65.4%, p=0.02). The percentage of individuals that needed physical restraint during hospital-stay among IA patients was also significantly higher (11.4% vs. 25.9%, p=0.01). Having any religious affiliations was significantly related to an IA status as well (OR=4-6.48).Conclusion: Our results suggest that cultural factors related to religious affiliations might play an important role in determining psychiatric hospitalization legal status. Religion might possibly influence someone's judgment and insight about his/her psychiatric disorder. This study restates the importance of dealing with the subject of religion with patients.